Pre-conditioning Strategies for Mesenchymal Stromal/Stem Cells in Inflammatory Conditions of Livestock Species - Uberti, Benjamin; Plaza, Anita; Henríquez, Claudio (Frontiers in Veterinary Science, 2022)
Mesenchymal stem/stromal cells (MSCs) therapy has been a cornerstone of regenerative medicine in humans and animals since their identification in 1968. MSCs can interact and modulate the activity of practically all cellular components of the immune response, either through cell-cell contact or paracrine secretion of soluble mediators, which makes them an attractive alternative to conventional therapies for the treatment of chronic inflammatory and immune-mediated diseases. Many of the mechanisms described as necessary for MSCs to modulate the immune/inflammatory response appear to be dependent on the animal species and source. Although there is evidence demonstrating an in vitro immunomodulatory effect of MSCs, there are disparate results between the beneficial effect of MSCs in preclinical models and their actual use in clinical diseases. This discordance might be due to cells´ limited survival or impaired function in the inflammatory environment after transplantation. This limited efficacy may be due to several factors, including the small amount of MSCs inoculated, MSC administration late in the course of the disease, low MSC survival rates in vivo, cryopreservation and thawing effects, and impaired MSC potency/biological activity. Multiple physical and chemical preconditioning strategies can enhance the survival rate and potency of MSCs; this paper focuses on hypoxic conditions, with inflammatory cytokines, or with different pattern recognition receptor ligands. These different preconditioning strategies can modify MSCs metabolism, gene expression, proliferation, and survivability after transplantation.